Physician support of HPV vaccination school-entry requirements. Issue 6 (2nd June 2016) - Califano, Sophia; Calo, William A.; Weinberger, Morris; Gilkey, Melissa B.; Brewer, Noel T.
ABSTRACT: School-entry requirements in the US have led to high coverage for several vaccines, but few states and jurisdictions have adopted these policies for human papillomavirus (HPV) vaccination. Because physicians play a key role in advocating for vaccination policies, we assessed physician support of requiring HPV vaccine for school entry and correlates of this support. Participants were a national sample of 775 physicians who provide primary care, including vaccines, to adolescents. Physicians completed an online survey in 2014 that assessed their support for school-entry requirements for HPV vaccination of 11 and 12 y olds. We used multivariable logistic regression to assess correlates of support for these requirements. The majority of physicians (74%) supported some form of school-entry requirements, with or without opt-out provisions. When opt-out provisions were not specified, 47% agreed that laws requiring HPV vaccination for school attendance were a "good idea." Physicians more often agreed with requirements, without opt-out provisions, if they: had more years in practice (OR=1.49; 95% CI: 1.09-2.04), gave higher quality HPV vaccine recommendations (OR=2.06; 95% CI: 1.45-2.93), believed that having requirements for Tdap, but not HPV, vaccination undermined its importance (OR=3.33; 95% CI: 2.26-4.9), and believed HPV vaccination was as or more important than other adolescent vaccinations (OR=2.30; 95% CI: 1.65-3.18). In conclusion, we found that many physicians supported school-entry requirements for HPV vaccination. More research is needed to investigate the extent to which opt-out provisions might weaken or strengthen physician support of HPV vaccination school-entry requirements.